2015
DOI: 10.1208/s12248-015-9727-7
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Novel Oral Cavity Compartmental Absorption and Transit Model for Sublingual Administration: Illustration with Zolpidem

Abstract: Abstract. Intraoral (IO) delivery is an alternative administration route to deliver a drug substance via the mouth that provides several advantages over conventional oral dosage forms. The purpose of this work was to develop and evaluate a novel, physiologically based oral cavity model for projection and mechanistic analysis of the clinical pharmacokinetics of intraoral formulations. The GastroPlus™ Oral Cavity Compartmental Absorption and Transit (OCCAT™) model was used to simulate the plasma concentration ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 38 publications
0
16
0
Order By: Relevance
“…The pH value in the oral cavity for healthy humans was found to be ~6.3-7.4, 43,44 while it decreased to weak acid condition for patients who suffered from oral C. albicans. In this research, in vitro release profile of AmB/MPP micelles and redissolved micelles (lyophilized powder redissolved in water) in different mediums (pH 5.8 and 6.8 and 0.5% SDS aqueous solution) was investigated ( Figure 3).…”
Section: In Vitro Release Of Micellesmentioning
confidence: 94%
“…The pH value in the oral cavity for healthy humans was found to be ~6.3-7.4, 43,44 while it decreased to weak acid condition for patients who suffered from oral C. albicans. In this research, in vitro release profile of AmB/MPP micelles and redissolved micelles (lyophilized powder redissolved in water) in different mediums (pH 5.8 and 6.8 and 0.5% SDS aqueous solution) was investigated ( Figure 3).…”
Section: In Vitro Release Of Micellesmentioning
confidence: 94%
“…The estimated zolpidem absorption via the oral mucosa was about 18% (Xia et al, 2015). In addition, the validation of the OCCAT model was also conducted for other intraoral drug delivery systems, such as sublingual solution (verapamil), and sublingual tablets (propranolol, asenapine, and nicotine) (Xia et al, 2015). The simulated oral transmucosal absorption portion was comparable with the observed data, except nicotine, a small molecule of low lipophilicity and high solubility, which was underestimated (Xia et al, 2015).…”
Section: Discussionmentioning
confidence: 60%
“…The results showed that the OCCAT model well captured the observed pharmacokinetics of zolpidem (R 2 > 0.9). The estimated zolpidem absorption via the oral mucosa was about 18% (Xia et al, 2015). In addition, the validation of the OCCAT model was also conducted for other intraoral drug delivery systems, such as sublingual solution (verapamil), and sublingual tablets (propranolol, asenapine, and nicotine) (Xia et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ACAT also considers the gastrointestinal tract as nine subsections, each with unique physicochemical properties, such as pH, allowed solubility, particle size, and permeability [93]. Novel developments have included other absorption routes other than the GI, which have been recently included in commercially available software, such as oral absorption for the development of sublingual zolpidem tablets [94]. The absorption constant (K a , expressed in terms of h −1 min −1 ), or also called first-order absorption rate constant (to not be confounded with pKa), is employed in most of the aforementioned models and is determined as a result from the changes in mass of absorbable drug over time at the site of administration.…”
Section: Adme Properties: Experimental Approaches and In Silico Modelmentioning
confidence: 99%